Antioxidant Ability of the 2% Indonesian Mount Lawu Propolis Ear Drops - Sudrajad, Hadi; Setiamika, Made; Hendradewi, Sarwastuti; Primadewi, Novi; Kandhi, Putu Wijaya; Pratiwi, Dewi; Kesumo, Aningdita; Pratiwi, Primadita Asis (Indonesian Journal of Pharmaceutical Science and Technology, 2025)
Propolis ear drops are natural antioxidants that have been developed for various health purposes. There are many types of propolis ear drops available today, including the Indonesian Mount Lawu Propolis ear drop (IMLPED). Indonesian Mount Lawu Propolis ear drop is proven to contain many antioxidant substances such as flavonoids, phenolic acids, caffeic acid pethyl ester, and quercetin. However, to date, no study has assessed the antioxidant activity of IMLPED, especially the 2% IMLPED. This study aims to assess the antioxidant activity of the 2% IMLPED. This is an in vitro study to assess the antioxidant activity of the 2% IMLPED with 2,2-Diphenyl-1-Picrylhydrazyl (DPPH) method based on the inhibitory concentration at 50% (IC50) value. The IC50 represents the concentration required to reduce 50% of the free radicals. The result of this study showed that the IC50 value of the 2% IMLPED is 30.71 µg/mL. Based on the IC50 value, the 2% IMLPED formula exhibits a robust antioxidant effect. The implications of this revelation establish IMLPED as a promising candidate in combating oxidative stress.